A study on waste management system at construction site in Klang Valley / Nurulain Abd Rashid - Abd Rashid, Nurulain (2011)
Construction industry was one of the important sectors that contribute to Malaysian economy. Construction process starts from designing stage until completion of the project. The construction activity include demolition, renovation, conservation, site clearing, bridges, roadway paving, new buildings such as school, houses and other infrastructures. These activities also would be the major of waste issues regarding from the construction waste. There are a large amount of construction waste is being produced by the construction sector. Waste minimization is important in the implementation in the construction industry The scope of this study covers the person in charge in the construction site such as the Site Supervisor, Site Manager and The Safety and Health Officer. The area for this case study is limited to Klang Valley area to study their construction waste management system at the construction site and the study was carried out by interviewing and observing the construction site. From the study, the construction waste management system in Klang Valley area were using the conventional system and they usually more considered about reducing the cost than reducing, recycle or reused the construction waste material back.